OPTIMISASI MULTIOBJEKTIF DALAM PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM DENGAN PENGUKURAN VALUE AT RISK (VAR) - Nanda Surya Jatnika; Esther Sorta Mauli Nababan (Journal of Fundamental Mathematics and Applications (JFMA), 2022)
When investors invest in their stock, the strategy used by an investor is to form an optimal portfolio of shares. An optimal stock portfolio can be created by utilizing the multi-objective optimization method, which can help investors achieve maximum return and minimum risk simultaneously. The multi-objective method has a weighting factor that acts as a risk indicator to assist investors in taking risks on the expected return. This study aims to optimize investors' profits and losses by forming an optimal stock portfolio using multi-objective and Value at Risk (VaR) measurements. The data used by the researcher is the weekly closing price of stocks which are always included in the LQ-45 stock index for the period 31 January 2019 – to 31 December 2020. The formed portfolio consists of three stocks, namely INCO.JK, MNCN.JK, and EXCL.JK. From the formed portfolio, the number of losses and profits obtained by investors can be seen based on the magnitude of the weighting coefficient k. Therefore, the greater the chance of profit (return), the greater the chance of loss (risk) that investors will receive.